Macrophage-derived extracellular vesicles regulate concanavalin A-induced hepatitis by suppressing macrophage cytokine production. (October 2020) - Kawata, Reo; Oda, Shingo; Koya, Yoshihiro; Kajiyama, Hiroaki; Yokoi, Tsuyoshi
Graphical abstract: Abstract: Acute liver failure is a clinical syndrome of severe hepatic dysfunction. Immune cells play an important role in acute liver failure. In recent years, the immunoregulatory function of extracellular vesicles (EVs) has been reported; therefore, it is inferred that EVs play a role in immune-mediated hepatitis. In this study, we investigated the immunoregulatory function of EVs in concanavalin A (Con A)-induced hepatitis. The mouse model was prepared by a single intravenous administration of 15 mg/kg Con A, in which there was a significant increase in the serum EVs number. In an in vitro study, the number of secreted EVs was also significantly increased in Con A-treated RAW264.7 cells, a mouse macrophage cell line, but not in Hepa1-6 cells, a mouse hepatoma cell line. In an in vitro EVs treatment study, EVs from Con A-treated mouse serum and Con A-treated RAW264.7 cells suppressed inflammatory cytokine production in Con A-stimulated RAW264.7 cells. miRNA sequencing analysis showed that the expression of mmu-miR-122-5p and mmu-miR-148a-3p was commonly increased in these EVs and EVs-treated cells. The pathways enriched in the predicted miRNA target genes included inflammatory response pathways. The mRNA levels of the target genes in these pathways (mitogen-activated protein kinase, phosphoinositide 3-kinase/Akt and Rho/Rho-associated coiled-coil containing protein kinase pathways) were decreased in the EVs-treated cells. In an in vivo RNA interference study, the knockdown of liver RAB27A, an EVs secretion regulator, significantly exacerbated Con A-induced hepatitis. These data suggest that macrophage-derived EVs play an important role in Con A-induced hepatitis through immunoregulation.